RETRACTED: Early Childhood Education Learning Model in Malaysia - Sitorus, Ahmad Syukri; Muhammad, Arifin; Jelita, Dea Putri; Aulia, Putri; Sayfriani, Angela; Zainuddin, Sahida Binti (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal Obsesi to article entitled